2016
DOI: 10.1002/adsc.201500764
|View full text |Cite
|
Sign up to set email alerts
|

Quest for Efficient Catalysts based on Zinc tert‐Butyl Peroxides for Asymmetric Epoxidation of Enones: C2vs C1‐Symmetric Auxiliaries

Abstract: Zinc tert-butyl peroxide-based catalysts for the asymmetric epoxidation of enones using tert-butyl hydroperoxide as an oxidant have been developed. Ac omparative study of chiral monoanioninc N,N'-bidentate ligands, C 2 -symmetric bisoxazolinates and C 1 -symmetric enaminooxazolinates,r evealed excellent performance of C 1 -symmetric auxiliary ligands on catalytic asymmetric epoxidation of enones (up to 96% yield, 91% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Moreover, we have also emphasized the essential role of the coordination state of the oxygenated organoaluminum and organozinc compounds, as well as the geometric requirements of an O 2 molecule approaching the metal centre . Apart from the fundamental aspects, these systematic studies have advanced rational design of metal alkyl/air systems as radical initiators for organic reactions, stoichiometric and catalytic asymmetric epoxidation of enones and pave the way to well‐defined metal alkoxides (not accessible through the classical alcoholysis path) as potential initiators of cyclic esters polymerization as well as to a new approach for the preparation of semiconductor zinc oxide quantum dots based on organozinc/air systems …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, we have also emphasized the essential role of the coordination state of the oxygenated organoaluminum and organozinc compounds, as well as the geometric requirements of an O 2 molecule approaching the metal centre . Apart from the fundamental aspects, these systematic studies have advanced rational design of metal alkyl/air systems as radical initiators for organic reactions, stoichiometric and catalytic asymmetric epoxidation of enones and pave the way to well‐defined metal alkoxides (not accessible through the classical alcoholysis path) as potential initiators of cyclic esters polymerization as well as to a new approach for the preparation of semiconductor zinc oxide quantum dots based on organozinc/air systems …”
Section: Introductionmentioning
confidence: 96%
“…Moreover,w eh ave also emphasizedt he essential role of the coordination state of the oxygenated organoaluminum [33,34] and organozinc [5,15,16,24] compounds, as well as the geometric requirementso fa nO 2 molecule approachingt he metal centre. [33,34] Apart from the fundamental aspects, these systematic studies have advanced rational designo fm etal alkyl/airs ystemsa sr adicali nitiators for organic reactions, [35][36][37] stoichiometric [38,39] and catalytic asymmetric epoxidation of enones [11,14,40] and pave the way to welldefined metal alkoxides (not accessible through the classical alcoholysis path) as potentiali nitiators of cyclic esters polymerization [25,41] as well as to an ew approach for the preparation of semiconductor zinc oxide quantum dots based on organozinc/ air systems. [42][43][44][45][46] Notably,t he oxygenationc hemistry of magnesium alkyls has remained anu ndeveloped area of research due to difficulties to control the respective reactions ystemsr esulting from the exceptionali nstability of MgOOR species.…”
Section: Introductionmentioning
confidence: 99%
“…Since Sharpless's groundbreaking discovery in the asymmetric epoxidation of the allylic alcohols mediated by TiOOR moieties, T MOOR‐type complexes have been extensively studied as intermediates in metal‐catalyzed oxidations of organic compounds . In turn, chemistry of NR M‐based alkylperoxides has flourished in recent years owing to their high catalytic activity in epoxidation of enones . Moreover, the latest discoveries demonstrated that oxygen‐centered radicals resulting from the O−O bond homolysis in NR MO−OR species are the key initiating species in radical organic reactions .…”
Section: Methodsmentioning
confidence: 99%
“…[3] In turn, chemistry of NR M-based alkylperoxides has flourished in recent years owing to their high catalytic activity in epoxidation of enones. [5,[18][19][20][21][22][23] Moreover,t he latest discoveries demonstrated that oxygen-centered radicals resulting from the O À Ob ond homolysis in NR MOÀOR species are the key initiating species in radical organic reactions. [24] Notably, NR MOOR systems have remained elusive since Franklandspioneering studies in 1849 (see below), and their isolation has proven challenging.…”
mentioning
confidence: 99%
“…Several other transitional metals catalysts have also been reported for efficient epoxidation reaction of chalcone derivatives. There are ethylperoxy zinc complex {[N{(C 3 F 7 )C(Cy)N} 2 ]Zn(μ-OOEt)} 2 (7) [110], zinc alkylperoxide/TBHP [111], zinc metal based tert-butyl peroxides (8) [112], chiral cobalt(III) complexes [113][114][115] [117], nickel Schiff base complex namely (Cr)NH 2 -MIL-101-PI-Ni (9) (Fig. 4) [118].…”
Section: Transition Metals Based Catalystmentioning
confidence: 99%